User Experience, Perceived Quality, and Service Quality as Determinants of E-Commerce Loyalty Mediated by Trust - Ahmad Sopyan; Nanda Pramana Putra; Nanda Fathiyah Gumay; Suharto Suharto (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study examines the effects of user experience, perceived quality, service quality, and customer engagement on customer loyalty, emphasizing the mediating role of consumer trust in e-commerce. Customer engagement is a direct driver of loyalty and an indirect factor that strengthens trust. Research Methodology: A quantitative approach was used to collect data from 389 e-commerce users via an online survey. Structural Equation Modeling (SEM) was used to analyze the relationships among the variables. Results: User experience, perceived quality, and service quality significantly enhance consumer trust, which positively affects customer loyalty. Customer engagement plays a dual role, directly influencing loyalty and indirectly shaping it through trust, confirming trust as a key mediator. Conclusions: User experience, perceived quality, service quality, and customer engagement significantly affect consumer trust. User experience, perceived quality, and customer engagement significantly influenced customer loyalty, whereas service quality showed no significant direct effect. Limitations: This study is Limited to Indonesian e-commerce and cross-sectional data. This study highlights engagement as a critical mechanism for building trust and sustaining loyalty. Contributions: This study contributes to the literature by demonstrating that user experience, perceived quality, service quality, and customer engagement jointly influence customer loyalty through consumer trust. This indicates that e-commerce platforms should prioritize enhancing experience, quality, and engagement to build and maintain trust and loyalty.